Effects of Catalyst Ball-Milling Process and Support on Synthesis of Carbon Nanotubes Over Fe Commercial Nanoparticles - Taleshi, F.; A. Hosseini, Ali; Pashaee, M.; Sohrabi, L. (Asian Journal of Chemistry, 2012)
This research was carried out to determine the growth of carbon nanotubes (CNTs) on Fe nanoparticles without carbon shell [Fe (nm), size < 60 nm], Fe nanoparticles with carbon shell [Fe* (nm), size < 60 nm], Fe* (nm)/Al2O3 and Fe* (nm)/MgO catalysts by chemical vapour deposition (CVD) method. Preparation of supported nanoparticles for growth of carbon nanotubes was carried out by mixing commercial Fe* nanoparticles (as catalyst) with Al2O3 and MgO powders (as supports) using ball-milling method. The quality of carbon nanotubes grown was compared using scanning electron microscopy (SEM) images and scanning electron microscopy patterns. Results indicated that, the preparation of nanoparticles/supports by ball-milling method could increase the range of growth temperature from 865-975 ºC. In addition, it can also have negative effects on diameter and morphology of synthesized carbon nanotubes at 925 ºC.